Formation of a gate dielectric of nanometer thickness by rapid thermal treatment - N. S. Kovalchuk; A. A. Omelchenko; V. A. Pilipenko; V. A. Solodukha; D. V. Shestovski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Investigations of the thickness and optical characteristics of thin SiO2 films obtained by one-, two-, or three-stage rapid thermal processing (RTP) at atmospheric pressure, pulses of 6, 12, and 20 s duration have been carried out. To obtain thin SiO2 films by the RTP method, N-type:Ph 4.5 Оhm/□ (100) silicon wafers were used as initial samples. The samples were preliminarily oxidized at 1000 °C of the obtained wet oxygen (SiO2 d = 100 nm), then the silicon oxide was completely removed in a solution of hydrofluoric acid, after which the wafers were subjected to chemical cleaning using the Radio Corporation of America (RCA) technology. Oxidation in a stationary oxygen atmosphere was carried out in one or two stages by heating the plates with a light pulse of different power up to maximum temperatures of 1035 – 1250 °C, as well as a three-stage process, where the final stage was annealing in a nitrogen atmosphere or in a forming gas (N2 97% + H2 3%). The characteristics of SiO2-Si barrier structures nitrided in N2, obtained by the RTP process by light fluxes with pulses of a second duration, were studied to improve the electrophysical parameters of gate oxides by the RTP method. It is of interest for integrated circuits (ICS) with a high density of the active regions of devices.